URGENSITAS MANAJEMEN BIMBINGAN DAN KONSELING DI SEKOLAH - Nengsi; Solita Anggraeni Susanti; Mariana Astuti; Hanin Ulya; Fitri Aulia; Rostina Andriyanti; Reza Agustina; Saopian Azhari; Mariani; Hesya Fadila Imtiyaz; Yeni Sulistiawarni; Sifa’yah; Nanang Ervia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Guidance and counseling management plays a strategic role in ensuring that guidance and counseling services in schools are implemented systematically, relevantly, and sustainably. However, the implementation of counseling services still faces various problems, including planning that is not fully based on students' needs, suboptimal organization, and limited continuous supervision and evaluation. This study aims to analyze the urgency of guidance and counseling management in schools and identify its role in supporting the effectiveness and sustainability of counseling services. This study employed a qualitative approach using a literature review method. Data were obtained from relevant scientific literature and analyzed through thematic analysis and narrative synthesis. The results indicate that the urgency of guidance and counseling management lies in the integration of needs-based planning, resource organization and collaboration among school components, systematic and responsive service implementation, as well as continuous supervision and evaluation. Guidance and counseling management functions not merely as an administrative activity but as a strategic system that supports students' optimal development and improves the quality of counseling services. Therefore, strengthening data-based, collaborative, and sustainable guidance and counseling management is essential in the implementation of counseling services in schools.